2009
DOI: 10.1177/147323000903700612
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Stress Hormone Response, Interleukin-6 and Anaesthetic Characteristics of Two Anaesthetic Techniques: Volatile Induction and Maintenance of Anaesthesia using Sevoflurane versus Total Intravenous Anaesthesia using Propofol and Remifentanil

Abstract: This prospective randomized study compared the effects of two types of anaesthesia on peri-operative anaesthetic profiles from induction to recovery and on immunological and neurohormonal responses to anaesthesia and surgical stress. Forty patients were assigned to undergo either volatile induction and maintenance of anaesthesia (VIMA) with sevoflurane or total intravenous anaesthesia (TIVA) with propofol and remifentanil. Plasma adrenaline, noradrenaline, cortisol, glucose and interleukin-6 (IL-6) levels were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
3
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 40 publications
(40 reference statements)
3
34
3
2
Order By: Relevance
“…Unlike our results, Ihn et al [12] detected higher level of epinephrine, norepinephrine, cortisol and glucose in the inhalation group compared to TIVA group, which reveals a better control of metabolic response using intravenous drugs.…”
Section: Discussioncontrasting
confidence: 56%
“…Unlike our results, Ihn et al [12] detected higher level of epinephrine, norepinephrine, cortisol and glucose in the inhalation group compared to TIVA group, which reveals a better control of metabolic response using intravenous drugs.…”
Section: Discussioncontrasting
confidence: 56%
“…It has been demonstrated that the total intravenous anesthesia using propofol and remifentanil suppresses the inflammatory response caused by surgery, to a greater extent than a balanced inhalation technique [9]. Ihn et al concluded that there are still controversies about which anesthetic technique best suppresses the inflammatory and immunological responses.…”
Section: Discussionmentioning
confidence: 99%
“…sevoflurane, isoflurane, enflurane, etc. and an opioid) (Schricker et al, 2000;Ledowski et al, 2005;Ihn et al, 2009;Kostopanagiotou et al, 2010;Marana et al, 2010). TIVA, consisting of a combination of propofol and morphine, was used in our experiment (for details see in section "Anaesthesia and medication").…”
Section: Anaesthesia Influence On Adrenal Hormones Secretionmentioning
confidence: 99%
“…It improves decreased sympathetic activity alpha and beta adrenergic receptors (Krzych et al, 2009). Combination of propofol and morphine (or other opioid) decreasing catecholamines and glucocorticoid released to blood (Fragen et al, 1987;Schricker et al, 1999Schricker et al, , 2000Ihn et al, 2009). The propofol/opioid combination suppresses HPA activity at each level.…”
Section: Anaesthesia Influence On Adrenal Hormones Secretionmentioning
confidence: 99%